Development of a mathematics teaching module based on the realistic mathematics education (RME) approach for grade VII algebra material at MTs Negeri Gowa - Nur A’laa Ihsan; Sri Sulasteri; Nur Khalisah Latuconsina (Universitas Muhammadiyah Enrekang, 2025)
This study examines the development process of an instructional module based on the Realistic Mathematics Education (RME) approach for teaching algebra to Grade VII students at MTs Negeri Gowa, as well as evaluates the quality of the resulting product in terms of validity, practicality, and effectiveness. The research employed a Research and Development (R&D) design following the ADDIE model, which consists of five phases: Analysis, Design, Development, Implementation, and Evaluation. The product developed in this study was a mathematics teaching module grounded in the RME approach for algebraic content. The trial subjects included 21 Grade VII students at MTs Negeri Gowa. The instruments used to assess the module included expert validation sheets, student activity observation sheets, teacher activity observation sheets, student response questionnaires, teacher response questionnaires, and a learning achievement test. The expert validation results yielded a coefficient of 0.87, which falls within the “very high” validity category (0.80 < V ≤ 1.00). The module demonstrated a high degree of practicality, indicated by an average positive response rate of 95.8% from the teacher and 90.4% from students both categorized as “highly positive.” The module also met the criteria for effectiveness, as shown by: (1) an average teacher activity score of 3.77, classified as “very good”; and (2) student learning mastery reaching 85%, placing it in the “high” category and meeting the classical mastery threshold.Overall, the findings indicate that the RME-based mathematics instructional module for Grade VII algebra at MTs Negeri Gowa satisfies the criteria of validity, practicality, and effectiveness based on the outcomes of the implementation phase.